Teen, Inc. - Petrucha, Stefan (Walker ; Distributed to the trade by Holtzbrinck Publishers, 2007)
Fourteen-year-old Jaiden has been raised by NECorp. since his parents were killed when he was a baby, so when he discovers that the corporation has been lying about producing illegal levels of mercury emissions, he and his two friends decide to try to do something about it.